RESPON OVARIUM SAPI LIMOUSIN DAN SIMMENTAL TERHADAP INDUKSI FOLLICLE STIMULATING HORMONE - Liamanu, Sukardi; Ngangi, Lentji Rinny; Turangan, Santie H.; Manopo, Jouke. H. (ZOOTEC, 2018)
OVARIUM RESPONSE OF LIMOUSIN COWS AND SIMMENTAL COWS ON  FOLLICLE STIMULATING HORMONE INDUCTION. To assess the effect of FSH administration on ovarian response rates. and to examine the effect of synchronizing follicular waves on ovarian response rates and the acquisition of embryos that are worthy of transfer. This research was carried out at the Laboratory of Embryo Production of Livestock Embryo Hall Cipelang Cijeruk district, Bogor regency, for 30 days. The materials used in this research were 50 cattle consisting of 25 female Limousin cows and 25 Simmental female cows at the aged around 5-7 years. They have given birth, and have been superovulated, at the body condition score (BCS) of 2.5-3.0, at the healthy and given forage and concentrate (BET protocol). FSH used was the Folltropin®-V brand superovulation with a dose of 20 mg / ml, the cement used was in accordance with the type of donor cow, with a concentration of 25 x 106 spermatozoa per straw. Primary data retrieval were done by observing the focal animal sampling technique requiring direct observation in the research location where the research material was located. The variables measured were response rate, number of corpus luteum (CL) in the left and right ovaries, the total collected embryos and ovum. Superovulation using Folltropin®-V in Simmental and Limousin cattle at Cipelang Livestock Embryo gave more significantly effect on Simmental cattle compared to Limousin cattle. Limousin and Simmental cattle supplemented with the hormone Folltropin®-V produced an average number of CL, embryos and ovum in Simmental cattle higher than Limousin cattle superovulated with FSH hormone. They have also a significant effect on the response rate, recovery rate, average CL number and the average number of embryos. The results obtained showed that Limousin and Simmental cattle differences significantly affected the number of collected embryos and ovum, the proportion of transferable embryos, Degenerate (Dg) embryo proportions and unfertilized proportion of Embryo Unfertilized (UF).Keywords: Limousin cows, Simmental cows, Superovulasi, FSH